Some considerations about alexia - Paredes, Víctor (1948)
Two words to offer this simple study that has its origin in the observation of a case of alexia complicated whose interest is not only in its extreme rarity among us, but also the polymorphous clinical picture that lends itself to multiple digressions teóric-practices.